تبیین فرهنگ سازمانی اداره کل ورزش و جوانان استان آذربایجان غربی با رویکرد نظری مدل دنیسون - میرحسن سیدعامری (Sport Sciences Research Institute, 2014)
Scholars have been investigating the culture of various organizations in order to find out how individuals' approach the organization. The present study was an attempt to determine various dimensions as well as the strengths and weaknesses of organizational culture and subculture in the Sports and the Youth Organization (SYO), West Azerbaijan. A total of 70 staff members of SYO in West Azerbaijan were selected purposefully. A background information questionnaire and the highly reliable (r= .82) Organization Culture Questionnaire (Denison, 2007) were applied for data collection purposes. The data, then, were analyzed based on Denison's Theoretical Framework and descriptive statistics. Results indicated that the SYO enjoys a good condition from consistency and mission point of view. However, it needs further developmental plans in terms of adaptability and involvement.  In addition, the obtained diagram of the organizational culture compared with that of Denison shows that there is a similarity between the two diagrams in terms of internal and external concentration; flexibility, nevertheless, remains static. Findings, furthermore, imply that staff behavior is affected by and adapted with the fundamental values of the organization.